2018
DOI: 10.2308/ajpt-52320
|View full text |Cite
|
Sign up to set email alerts
|

Audit Partner Identification and Characteristics: Evidence from U.S. Form AP Filings

Abstract: SUMMARY This paper investigates the overall impact of and the information made available by the recent audit partner disclosure requirement in the U.S. After a contentious comment period, the PCAOB released Rule 3211, which requires registered public accounting firms to disclose the name of the audit partner for every audit report it issues. In the first year of adoption, we find a significant increase in audit quality and audit fees and a significant decrease in audit delay. We collect information on partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 69 publications
8
99
3
Order By: Relevance
“…Consistent with prior studies (e.g. Burke et al 2019;Palvia et al 2015), the use of less optimistic language by female audit partners can be justified in view of their risk-averse attitude to reduce their legal liability exposure.…”
Section: The Tone and Readability Of Auditor's Report Analysissupporting
confidence: 73%
“…Consistent with prior studies (e.g. Burke et al 2019;Palvia et al 2015), the use of less optimistic language by female audit partners can be justified in view of their risk-averse attitude to reduce their legal liability exposure.…”
Section: The Tone and Readability Of Auditor's Report Analysissupporting
confidence: 73%
“…They conclude that disclosing engagement partners is associated with higher audit quality (as proxied by more audit effort and less aggressive financial reporting). Likewise, Burke, Hoitash, and Hoitash () found that the audit partner disclosure requirement leads to higher audit fees, higher audit quality, and shorter audit delays. They also indicated that audit partner characteristics, including gender, busyness, education, and social connections, are not associated with audit quality.…”
Section: Background and Prior Researchmentioning
confidence: 98%
“…Hossain et al (2016) finds using Australian evidence that female partners are less likely to issue GCOs for financially distressed firms. Hoitash et al (2019) reports no significant impact of female auditor on discretionary accruals and audit delay, using U.S. evidence.…”
Section: Literature Review: Auditor Gender and Audit Qualitymentioning
confidence: 98%
“…In general, using going concern opinions and abnormal accruals as indicators of audit quality, these studies find mixed evidence that auditor gender affects audit quality. Recently, with the release of engagement lead auditors names by Public Company Accounting Oversight Board (PCAOB), a number of studies have started to examine the relation between auditor gender and audit quality in the U.S. context (Lee, Nagy and Zimmerman 2019;Burke, Hoitash, and Hoitash 2019). However, using abnormal accruals, restatements, and audit delays as proxies for audit quality, these studies also provide mixed evidence that auditor gender affects audit quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation